"Silva rerum" w jednej osobie, czyli filozof Jan Kurowicki na literackiej ścieżce = "Silva rerum", within one person, that is philosopher Jan Kurowicki on a literary path - Kopa, Dawid (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The text analyses the role of poems in the structure of Jan Kurowicki`s monodrama "Pan Kepler raczy umierać" ["Mr Kepler Deigns to Be Dying"]. It inspires reflection on the way the read manifests in the written. The category of silva is related to the intellectual profile of the author. "Pan Kepler raczy umierać" is presented as a turning point in Jan Kurowicki`s literary career. It also indicates how the monodrama interrelates with different areas of the author`s creative output.
Keywords: Kurowicki, Jan (1943-2017); monodram; poezja; filozofia; literaturoznawstwo; monodrama; poetry; literary criticism; philosophy